Tingkat Minat Baca Siswa Dalam Gerakan Literasi KolaborasiMulti-Sektor di Desa Dayang Suri - Zulkarnain Zulkarnain; M. Falikul Daffa; Neftriana Nainggolan; Qotrunnada Salsabila; Febrianti Wulandari; Salshabila Nuresy; Dimas Irham Maulana; Ilham Al'madani; Rika Yulianti; Mohammad Djofi Maulana; Sri Hani'ainiyah; Fatma Saptadia Tri Manja (Unri Conference Series: Community Engagement, 2025)
Improving students' reading interest is one of the efforts to support the achievement of quality education, as part of the Sustainable Development Goals (SDGs). The 2025 Thematic Literacy Community Service Program (KUKERTA) by Universitas Riau, held in Dayang Suri Village, Bunga Raya Sub-district, Siak Regency, represents a tangible form of multisectoral collaboration in partnership with the National Library of Indonesia to promote a planned, structured, and sustainable literacy culture. This community service activity employed a quantitative descriptive approach. Data collection methods included observation, documentation, and the distribution of questionnaires to sixth-grade students at SDN 09 Dayang Suri who participated in the literacy activities. One of the key literacy initiatives was regular read-aloud sessions aimed at fostering students’ interest in reading, improving reading comprehension, and cultivating a literacy culture in the school. The results of the questionnaire indicate that 30% of students have a very good reading interest level, 40% are categorized as good, and 30% are categorized as adequate. This data is supported by the higher frequency of library visits, enthusiasm during the read-aloud sessions, and the growing confidence of students in reviewing the content of the texts they read. These findings provide an overview of the reading interest conditions of students in Dayang Suri Village, while also demonstrating the potential for multisectoral collaboration utilizing the school library and reading aloud activities as parts of efforts to support literacy and quality education.